2019
DOI: 10.15537/smj.2019.10.24322
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of ShotBlocker and cold spray in reducing intramuscular injection-related pain in adults

Abstract: ShotBlocker ‫مجموعات‬ ‫في‬ ‫أقل‬ VAS ‫درجات‬ ‫كانت‬ ‫النتائج:‬ ‫التحكم‬ ‫مجموعة‬ ‫في‬ ‫عنها‬ ‫مم)‬ 10( ‫البارد‬ ‫والرذاذ‬ ‫مم)‬ 11( ‫كبير‬ ‫‪VAS‬بشكل‬ ‫درجات‬ ‫تختلف‬ ‫لم‬ .)p=0.001( ‫مم)‬ 31( ‫ردود‬ ‫كشفت‬ ‫البارد.‬ ‫الرذاذ‬ ‫ومجموعات‬ ShotBlocker ‫بني‬ ‫الرش‬ ‫من‬ ‫أكثر‬ ‫إدارته‬ ‫الصعب‬ ‫من‬ ‫كان‬ ShotBlocker ‫أن‬ ‫املشغلني‬ ‫البارد.‬ ‫من‬ ‫تقلل‬ ‫فعالة‬ ‫دوائية‬ ‫غير‬ ‫وسيلة‬ ‫هو‬ ShotBlocker ‫اخلالصة:‬ ‫الرذاذ‬ ‫فعالية‬ ‫فعاليته‬ ‫وتشبه‬ IM ‫العضلي‬ ‫باحلقن‬ ‫املرتبط‬ ‫األلم‬ ‫البارد.‬ Objectives: To comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 19 publications
5
31
3
5
Order By: Relevance
“…As the vibration application is non‐pharmacological, it is a procedure that nurses can perform independently (Aslan, 2014; Özveren, 2011). Although there are many studies in the literature reporting that vibration and cold application reduce injection pain (Ballard et al, 2019; Bilge et al, 2019; Şahin & Eşer, 2018), the number of the studies conducted by applying vibration for adult patients is quite limited. In the study by Alshahwan, vibration and cold application were compared in reducing pain and it was stated that vibration was more effective in reducing pain (Alshahwan, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the vibration application is non‐pharmacological, it is a procedure that nurses can perform independently (Aslan, 2014; Özveren, 2011). Although there are many studies in the literature reporting that vibration and cold application reduce injection pain (Ballard et al, 2019; Bilge et al, 2019; Şahin & Eşer, 2018), the number of the studies conducted by applying vibration for adult patients is quite limited. In the study by Alshahwan, vibration and cold application were compared in reducing pain and it was stated that vibration was more effective in reducing pain (Alshahwan, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Visual Analog Scale, which is used to assess the level of pain and satisfaction, is a 10 cm scale with subjective descriptive expressions on both sides (0 cm: no pain/no pleasure at all and 10 cm: unbearable pain/very satisfied). In the present study, VAS was preferred due to its use in similar studies which examine pain and satisfaction together (Bilge et al, 2019; İnangil & İnangil, 2020; Şahin & Eşer, 2018). Pain and satisfaction were assessed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in another study by Bilge et al, they used cold spray for ice effect. After the application, they found that the cold spray was an effective attempt to reduce the pain associated with IM injection (26). Additionally, it has been reported in literature that beside its pain decreasing effects, cold applications could cause vasoconstriction and delays in the absorption of the drug, and that this should be taken into consideration in patients where the absorption of the drug needs to be fast (27).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, VAS scores of patients who experienced unintentional movement during dermal puncture were higher (1.44 ± 0.59 vs. 1.98 ± 0.58; P < 0.05). These results can be explained by the fact that pain assessment can be affected by negative expectations or anxiety (17,18).…”
Section: E35mentioning
confidence: 99%
“…The authors referred to the Gate Control Theory (22) for the immediate effects of the ShotBlocker for intramuscular injection pain (7,17,23,24). ShotBlocker could inhibit the transmission of action potentials from small-diameter fibers by activating inhibitory interneurons in the dorsal spinal roots with a tactile stimulation with multiple blunt points.…”
Section: E35mentioning
confidence: 99%